Two credulous notions for acceptance of arguments in abstract frameworks - Martínez, Diego C. (2006)
Abstract argumentation systems are formalisms for defeasible reasoning where some components remain unspecified, the structure of arguments being the main abstraction. In this work, we use an extended argumentation framework where two kinds of defeat relation are present, in order to define two basic semantic notions: a fixpoint operator and an argument extension based in the concept of progressive defeat paths. These mechanisms constitute a credulous approach to characterize sets of possible accepted arguments.